(3GdEYJeGO GdeSJfOj hGdJLGQI GdEdcJQhfjI (B/s - (3aGYhQ, eGRf YHO GdYRjRs ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 2006)
(3jVe GdGYJeGO GdeSJfOj hOhQg aj JWhjQ GdJLGQI GdOhdjI, GdBKGQ GdbGfhfjI GdfGTFI Yf GdGYJeGO GdeSJfOj, GdYdGbI Hjf GdeUQa hGdeSJajOs
(3HjHdjhZQGajG(B: (3U(B.375(3; edGMb(B: (3U(B. 229s
Keywords: (3GdGYJeGOGJ GdeSJfOjIs; (3GdJLGQI GdNGQLjIs